Establishment and psychometric characteristics of emotional words list for suicidal risk assessment in speech emotion recognition - Shen, Juan; Zhang, Shuo; Tong, Yongsheng; Dong, Xiangmin; Wang, Xuelian; Fu, Guanghui; Zhao, Liting; Wu, Mengjie; Yin, Yi; Wang, Yuehua; Liu, Nancy H.; Wu, Jianlan; et al. (Frontiers in Psychiatry, 2022)
Background: Emotional disturbance is an important risk factor of suicidal behaviors. To ensure speech emotion recognition, a novel technique to evaluate emotional characteristics of speech, precision in labelling emotional words is a prerequisite. Currently, a list of suicide-related emotional word is absent. The aims of this study were to establish an Emotional Word List for Suicidal Risk Assessment (EWLSRA) and test the reliability and validity of the list in a suicide-related speech emotion recognition task. Methods: Suicide-related emotion words were nominated and discussed by 10 suicide prevention professionals. Sixty-five tape-recordings of calls to a large psychological support hotline in China were selected to test psychometric characteristics of the EWLSRA. Results: The results shows that the EWLSRA consists of 11 emotion words which were highly associated with suicide risk scores and suicide attempts. Results of exploratory factor analysis support one-factor model of this list. The Fleiss’ Kappa value of 0.42 indicated good inter-rater reliability of the list. In terms of criteria validities, indices of despair (Spearman ρ=.54, P<.001), sadness (ρ=.37, P=.006), helplessness (ρ=.45, P=.001), and numbness (ρ=.35, P=.009) were significantly associated with suicidal risk scores. The index of the emotional word of numbness in callers with suicide attempt during the 12-month follow-up was significantly higher than that in callers without suicide attempt during the follow-up (P=.049). Conclusions: This study demonstrated that the EWLSRA has adequate psychometric performance in identifying suicide-related emotional words of recording of hotline callers to a national wide suicide prevention line. This list can be useful for speech emotion recognition in future studies on suicide prevention.